2006
DOI: 10.1007/s11090-006-9011-9
|View full text |Cite
|
Sign up to set email alerts
|

Methanol and Dimethyl Sulfide Removal by Pulsed Corona Part I: Experiment

Abstract: Methanol and dimethyl sulfide are volatile organic compound (VOC) air pollutants that are subject of severe environmental regulations due to their toxicity, environmental persistence and odor. Traditional technologies are often inefficient for their removal, especially in the case of the dilute industrial streams. Non-thermal plasma methods, typically characterized by high removal efficiency, energy yields and good economy, offer possible alternative solutions. The present research employs pulsed corona discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…Experimental data shown in this figure also suggest that the CO concentration starts to level off when SED approaching at 500 J/l, after an initial increase with SED. This result is different from the one obtained by Lock et al [15], who found that CO concentration increases monotonically with SED. On the other hand, the result shown in Fig.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Experimental data shown in this figure also suggest that the CO concentration starts to level off when SED approaching at 500 J/l, after an initial increase with SED. This result is different from the one obtained by Lock et al [15], who found that CO concentration increases monotonically with SED. On the other hand, the result shown in Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Similar argument has been reported previously [16,17]. However, a strong link between the production of CO and CO 2 has also been reported in other experiments [15,[18][19][20][21]. Therefore, more detailed assessment of the experimental conditions and theoretical analysis by chemical kinetics are needed to understand this discrepancy.…”
Section: Resultssupporting
confidence: 83%
“…Clopidogrel is a thiophene pyridine prodrug that needs to be absorbed by the intestines and transformed into active components by the metabolism of various enzymes in the liver to exert its platelet anti-aggregation effect [ 26 ]. The P-glycoprotein (P-gp), encoded by the ABCB1 gene, regulates clopidogrel absorption in the small intestine [ 27 ]. P-gp is a transmembrane protein with the primary function of pumping the drug out of the cell and into the blood circulation.…”
Section: The Pharmacological Effects Of Clopidogrelmentioning
confidence: 99%
“…Then, water-washing and air-dilution systems were found very effective to reduce odor at the idling condition of the engine. Lock et al (2006) present experimental data on removal of methanol and dimethyl sulfide, air pollutants that are subject of severe environmental regulations due to their toxicity, environmental persistence and odor, from dry and humid air streams by non-thermal plasma methods.…”
Section: Odor Case Studiesmentioning
confidence: 99%